2015
DOI: 10.1584/jpestics.d14-086
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of novel acaricide pyflubumide: Effects on the mitochondrial respiratory chain

Abstract: This study aimed to determine the mode of action of pyflubumide, a novel acaricide under development by Nihon Nohyaku Co., Ltd. Because of its structural similarity to succinate-dehydrogenase inhibitor (SDHI) fungicides, its ability to inhibit mitochondrial complex II was investigated. Pyflubumide exhibited low inhibitory activity on spider mite mitochondria; conversely, its deacylated metabolite (NH-form) showed high mitochondrial inhibitory activity. Pyflubumide was quickly metabolized to its NH-form in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 24 publications
2
32
0
1
Order By: Relevance
“…Taking into consideration the possible decomposability of these functional groups, the excellent activity of less-hindered acyl-substituted In fact, when pyflubumide was incubated with spider mite (T. urticae) homogenate, its deacylated derivative 9 was observed. 20) This result strongly supports our hypothesis that the deacylated derivatives would be the active forms and excellent acaricidal activity is derived by improving penetration and metabolic activation.…”
Section: Amide Bridgesupporting
confidence: 86%
See 2 more Smart Citations
“…Taking into consideration the possible decomposability of these functional groups, the excellent activity of less-hindered acyl-substituted In fact, when pyflubumide was incubated with spider mite (T. urticae) homogenate, its deacylated derivative 9 was observed. 20) This result strongly supports our hypothesis that the deacylated derivatives would be the active forms and excellent acaricidal activity is derived by improving penetration and metabolic activation.…”
Section: Amide Bridgesupporting
confidence: 86%
“…21,22) However, it was also suggested that their binding sites on mitochondrial complex II and/ or the manners of binding are not identical. 20,23,24) These results demonstrate that pyflubumide could be a promising new acaricide. Pyflubumide has been tested in official trials with the code number NNI-0711 in Japan since 2007, and a registration petition for this acaricide has already been made in 2012.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to cyenopyrafen and cyflumetofen, it was found that pyflubumide is a pro-acaricide, with its metabolite exhibiting high inhibitory activity on mitochondrial complex II. Interestingly, its binding manner was suggested to be different than that from cyenopyrafen, but detailed data to support this claim are currently lacking [82,95].…”
Section: Novel Complex II Inhibitorsmentioning
confidence: 99%
“…Metabolic activation occurs through an N‐dealkylation of a small alkyl ether to form the secondary amide active compound (Fig. ) …”
Section: Examples Of Proinsecticides (Organized By Irac Group)mentioning
confidence: 99%